International Harmonization of Nomenclature and Diagnostic Criteria (INHAND): Progress to Date and Future Plans. (July 2015) - Keenan, C. M.; Baker, J.; Bradley, A.; Goodman, D. G.; Harada, T.; Herbert, R.; Kaufmann, W.; Kellner, R.; Mahler, B.; Meseck, E.; Nolte, T.; Rittinghausen, S.; et al.
The International Harmonization of Nomenclature and Diagnostic Criteria for Lesions in Rats and Mice proposal (INHAND) has been operational since 2005. A Global Editorial Steering Committee manages the overall objectives of the project, and the development of harmonized terminology for each organ system is the responsibility of the Organ Working Groups, drawing upon experts from North America, Europe, and Japan. Great progress has been made with 9 systems published to date—respiratory, hepatobiliary, urinary, central/peripheral nervous systems, male reproductive and mammary, zymbals, clitoral, and preputial glands in Toxicologic Pathology and the integument and soft tissue and female reproductive in the Journal of Toxicologic Pathology as supplements and on a Web site—www.goReni.org . INHAND nomenclature guides offer diagnostic criteria and guidelines for recording lesions observed in rodent toxicity and carcinogenicity studies. The guides provide representative photomicrographs of morphologic changes, information regarding pathogenesis, and key references. The purpose of this brief communication is to provide an update on the progress of INHAND.